The First Triangular Representation of The Symmetric Groups over a field K of characteristic pdivides (n-2) - Al-Aamily, Eyad M.A; M.Al-Butaihi, Ali Abdulsahib; Ta,ai, Abid Ali HAl (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper we will study the new type of triangular representations of the symmetric groups which is called the first triangular representations of the symmetric groups over a field K of characteristic pdivides(n-2).